«Aquel día en que cantó la gallina»: an ecocritical reading of Fabla salvaje - Favaron Peyón, Pedro (2023)
This article proposes a reading of the short novel Fabla salvaje (1923) from the point of view of ecocriticism. Although this work has an inescapable psychological plot, the different psychological passages through which the main character (Balta Espinar) goes through have a correlation with natural phenomena which, in turn, seem to correspond to certain Amerindian cosmogonies. Vallejo’s narrative evidences an indigenous poetics that understands other beings as bearers of agency and spirit; however, the characters’ relationship with the territory, which at first appears harmonious, soon reveals itself to be hostile and disturbing. Fabla salvaje can be read, precisely, as the dramatic testimony of a transculturated subject incapable of resuming a healthy link with the native geography; in this sense, it can be proposed that Balta Espinar is an alterego of Vallejo and his conflictive relationship with the native village, the feminine, paternity and nature.